The improvement of functional food in yogurt enriched with purple sweet potato (Ipomea batatas var. Ayamurasaki) - Afiati, F.; Priadi, G.; Setiyoningrum, F. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
he research was conducted to examine the use of purple sweet potato (Ipomoea batatas var. Ayamurasaki) to improve functional food of yogurt. This experiment has 2 factors of treatments. The first factor (i) was concentration of skim milk, i.e. 0%, 3% and 6%; the second factor (ii) was concentration of purple sweet potato, i.e. 0%, 2% and 4% of purple sweet potato. The parameters observed were viability of lactic acid bacteria (LAB), pH, moisture content, protein, fat, carbohydrate, ash and crude fiber and organoleptic. The results showed that there was no interaction between the concentration of skim-milk and the purple sweet potato on total LAB, moisture content and crude fiber. However, the interaction occurred on the levels of fat, protein, carbohydrate and ash. The organoleptic test results that yogurt enriched by 2% purple sweet potato without addition of skim was more preferable by panelist with a value of 3.65.